The Jews in medieval Egypt - Frenḳel, Miryam 1950- (The lands and ages of the Jewish people, 2021)
Between the Hellenistic World and the Cairo Genizah: The Jewish Community in Late Antique Egypt / Tal Ilan -- A Concise History of Islamic Egypt / Yehoshua Frenkel -- The Community's Borders; Converts and Renegades / Moshe Yagur -- Communal Self-Government: The Genizah Period / Mark R. Cohen -- Introduction to the Legal Arena / Oded Zinger -- Jewish Economic Life in Medieval Egypt: Images, Theories, and Research / Jessica Goldberg -- Jewish Family Life in Medieval Egypt / Miriam Frenkel -- Situating Egyptian Pietism / Elisha Russ-Fishbane -- Languages and Language Varieties Used by Medieval Egyptian Jews / Esther-Miriam Wagner -- Hebrew Poetry in Medieval Egypt / Joseph Yahalom -- The Last Phase-The Jews in Medieval Egypt under the Mamluks (1250-1517) / Amir Mazor